A comparison of professional versus citizen journalistic roles: Views from visual journalists. (February 2020) - Chung, Deborah S; Kim, Yung Soo; Nah, Seungahn
Using a Web-based survey targeting visual professionals, this study examines their professional role conceptions along with their views on emerging visual citizen contributors' roles. While participants' ratings of the two groups' roles were generally correlated within each group, no correlations resulted between the two groups with the exception of the civic roles. Further, visual professionals rated their roles as significantly more important for all five roles. When assessing views on citizen-contributed visuals, it was clear that participants evaluated them with a critical eye, expressing dislike toward citizens' visual contributions and deeming them a threat to their livelihood.